2015
DOI: 10.5505/tjb.2015.27146
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polyphenol oxidase during three ripening stages of an eggplant (Solanum melongena L.) fruit: a local type in northeast Anatolia

Abstract: Characterization of polyphenol oxidase during three ripening stages of an eggplant (Solanum melongena L.) fruit: a local type in northeast Anatolia[Patlıcan (Solanum melongena L.) meyvesinin polifenol oksidazının üç olgunlaşma safhası boyunca karakterizasyonu: Doğu Anadolu' da yerel bir tip] ABSTRACT Objective: A relatively new local type of eggplant, Solanum melongena L. 'Kadife' is widely consumed in Turkey because of its economic availability and good nutritional qualities. However, the high polyphenol cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…K m values for other substrates smoothly increased but V max decreased. K m values reported in previous studies in literature for mushroom (Colak et al, ; Espin, Leeuwen & Wichers, ; Kolcuoğlu et al, ) and other organisms (Liu et al, ; Torun et al, ) showed that Lac PPO has great substrate affinity. For most biotechnologically important enzymes, K m values varied within the range of 10 −1 –10 −5 M (Fullbrook, ).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…K m values for other substrates smoothly increased but V max decreased. K m values reported in previous studies in literature for mushroom (Colak et al, ; Espin, Leeuwen & Wichers, ; Kolcuoğlu et al, ) and other organisms (Liu et al, ; Torun et al, ) showed that Lac PPO has great substrate affinity. For most biotechnologically important enzymes, K m values varied within the range of 10 −1 –10 −5 M (Fullbrook, ).…”
Section: Resultsmentioning
confidence: 69%
“…K m values for other substrates smoothly increased but V max decreased. K m values reported in previous studies in literature for mushroom Espin, Leeuwen & Wichers, 1999;Kolcuoğlu et al, 2007) and other organisms (Liu et al, 2013;Torun et al, 2015) showed that…”
Section: Kinetic Characteristics Of Lacppomentioning
confidence: 72%
See 2 more Smart Citations
“…This catalytic characteristic assists in the fruit maturation. Similar is the effect produced in the amylase, pectinase, and cellulase reactions, which are often used for the conversion of polysaccharides into oligo and monosaccharides (Torun et al, 2015).…”
Section: Introductionmentioning
confidence: 68%